Modulation of Morphine Analgesia, Antinociceptive Tolerance, and Mu-Opioid Receptor Binding by the Cannabinoid CB2 Receptor Agonist O-1966 - Reichenbach, Zachary W.; DiMattio, Kelly; Rajakaruna, Suren; Ambrose, David; Cornwell, William D.; Tallarida, Ronald J.; Rogers, Thomas; Liu-Chen, Lee-Yuan; Tuma, Ronald F.; Ward, Sara Jane (Frontiers in Pharmacology, 2022)
Acutely, non-selective cannabinoid (CB) agonists have been shown to increase morphine antinociceptive effects, and we and others have also demonstrated that non-selective CB agonists attenuate morphine antinociceptive tolerance. Activation of cannabinoid CB2 receptors reverses allodynia and hyperalgesia in models of chronic pain, and co-administration of morphine with CB2 receptor selective agonists has been shown to be synergistic. CB2 receptor activation has also been shown to reduce morphine-induced hyperalgesia in rodents, an effect attributed to CB2 receptor modulation of inflammation. In the present set of experiments, we tested both the acute and chronic interactions between morphine and the CB2 receptor selective agonist O-1966 treatments on antinociception and antinociceptive tolerance in C57Bl6 mice. Co-administration of morphine and O-1966 was tested under three dosing regimens: simultaneous administration, morphine pre-treated with O-1966, and O-1966 pre-treated with morphine. The effects of O-1966 on mu-opioid receptor binding were determined using [3H]DAMGO and [35S]GTPS binding assays, and these interactions were further examined by FRET analysis linked to flow cytometry. Results yielded surprising evidence of interactions between the CB2 receptor selective agonist O-1966 and morphine that were dependent upon the order of administration. When O-1966 was administered prior to or simultaneous with morphine, morphine antinociception was attenuated and antinociceptive tolerance was exacerbated. When O-1966 was administered following morphine, morphine antinociception was not affected and antinociceptive tolerance was attenuated. The [35S]GTPS results suggest that O-1966 interrupts functional activity of morphine at the mu-opioid receptor, leading to decreased potency of morphine to produce acute thermal antinociceptive effects and potentiation of morphine antinociceptive tolerance. However, O-1966 administered after morphine blocked morphine hyperalgesia and led to an attenuation of morphine tolerance, perhaps due to well-documented anti-inflammatory effects of CB2 receptor agonism.